Healthcare utilization of people with AK. (1st September 2019) - Noels, E.C.; Hollestein, L.M.; van Egmond, S.; Lugtenberg, M.; van Nistelrooij, L.P.J.; Bindels, P.J.E.; van der Lei, J.; Stern, R.S.; Nijsten, T.; Wakkee, M.
Summary: Actinic keratoses (AK) are rough skin lesions (patches) caused by long‐term sun exposure in people with light skin. The prevalence of AK is high, affecting 24‐60% of people above the age of 50. Having many AKs is a sign that a person may be more likely to develop skin cancer. This study, from the Netherlands, aimed to provide insight in the management (treatment) of AKs, by describing how healthcare services are used by people with AK, and its management by GPs and dermatologists. The authors found that a large proportion of people with AK are not aware of having AK, and thus not aware of an increased skin cancer risk. Its treatment at the GP largely seems inconsistent with guidelines, and 31% are directly referred to the dermatologist at the first GP appointment. These referrals are usually not related to the extensiveness of the AK, meaning how many AKs the person has. This causes a high burden in secondary care (e.g. hospitals, where people are referred to dermatologists) with patients who could be easily treated by the GP. At the dermatologists there is a high rate of follow‐up of patients with AK, meaning they come back for further appointments. The authors conclude that their findings indicate inefficient use of healthcare resources. They suggest that to overcome this, motives of GPs and dermatologists for diverging from current guidelines in the management of AK need to be explored.